A review of urban ecosystem services research in Southeast Asia - Lourdes, Karen T.; Gibbins, Chris N.; Hamel, Perrine; Sanusi, Ruzana; Azhar, Badrul; Lechner, Alex Mark (Multidisciplinary Digital Publishing Institute, 2021)
Urban blue-green spaces hold immense potential for supporting the sustainability and liveability of cities through the provision of urban ecosystem services (UES). However, research on UES in the Global South has not been reviewed as systematically as in the Global North. In Southeast Asia, the nature and extent of the biases, imbalances and gaps in UES research are unclear. We address this issue by conducting a systematic review of UES research in Southeast Asia over the last twenty years. Our findings draw attention to the unequal distribution of UES research within the region, and highlight common services, scales and features studied, as well as methods undertaken in UES research. We found that while studies tend to assess regulating and cultural UES at a landscape scale, few studies examined interactions between services by assessing synergies and tradeoffs. Moreover, the bias in research towards megacities in the region may overlook less-developed nations, rural areas, and peri-urban regions and their unique perspectives and preferences towards UES management. We discuss the challenges and considerations for integrating and conducting research on UES in Southeast Asia based on its unique and diverse socio-cultural characteristics. We conclude our review by highlighting aspects of UES research that need more attention in order to support land use planning and decision-making in Southeast Asia.